Deployment of a Testbed for Validation of TSN Networks in Avionics - Laura Castro-Lara; Pablo Vera-Soto; Sergio Fortes; Vicente Escaño; Rafael Ortiz; Raquel Barco (Aerospace)
Time-Sensitive Networking (TSN) in avionics is being considered as a standard capable of providing more real-time and safety-critical capabilities than AFDX, the current standard in avionics communications. A TSN profile is therefore being developed for the aerospace domain by IEEE. Hence, this research outlines the deployment of a testbed aimed at validating TSN in avionics to ensure that this technology meets the stringent timing and latency requirements of avionics applications. To this end, a daisy chain or ring topology has been set up for the validation of the testbed, as this topology provides redundancy of paths without the need to add additional devices. This work presents latency and jitter measurements under different priority configurations and different channel saturation conditions, showing no packet loss and demonstrating the reliability of TSN for time-critical applications. A comparison with Avionics Full Duplex Ethernet (AFDX) simulations was also made, highlighting the weaknesses of AFDX. By providing a comprehensive platform for testing and validation, the testbed will contribute to the advancement of TSN technology in aerospace applications, ultimately improving the safety and efficiency of aircraft operations.